Convective Heat Transfer in Heat Exchanger Using Nanofluids -A Review - D., Madhesh; V., Leelavinodhan; P., Ramanathan; A.R., Sivaram (INTI International University, 2023)
In the recent scenario, nanofluids play a major role in the heat transfer enhancement of heat exchangers due to their fascinating thermophysical properties and other potential benefits. The heat transfer characteristics of nanofluids were improved by incorporating a very small quantity of nanoparticles in the base fluid. A new correlation has been proposed for the selected nanofluids with performance analysis. The parameters like volume concentration, particle size, and base fluid properties are analyzed in the compact heat exchanger. Instead of using the helical coil heat exchanger instead of the straight tube type leads to an enhancement in the Nusselt number. Most of the researchers reported that the pumping power decreases by increasing the concentration at a constant mass flow rate. This paper, discussed the numerical and experimental investigations of heat transfer using nanofluids in heat exchanger applications. The latest works of literature on nanofluids have been presented in this paper. Moreover, as summarized nanotechnology is a promising field in sustainable energy to reduce energy consumption for the optimum design of heat exchangers.